Surgical Management of Small Bowel Crohn's Disease - Chandrasinghe, Pramodh (Frontiers in Surgery, 2022)
Crohn's disease in the small bowel could present itself as an inflammatory stricture, a fibrotic stricture as penetrating disease or a combination of both. It is pertinent to differentiate the disease process as well as its extent to effectively manage the disease. Currently, a combination of medical and surgical therapies forms part of the treatment plan while the debate of which therapy is better continues. In managing the strictures, identification of the disease process through imaging plays a pivotal role as inflammatory strictures respond to anti-tumor necrosis factor (TNF) and biological agents, while fibrotic strictures require endoscopic or surgical intervention. Recent evidence suggests a larger role for surgical excision, particularly in ileocolic disease, while achieving a balance between disease clearance and bowel preservation. Several adaptations to the surgical technique, such as wide mesenteric excision, side to side or Kono-S anastomosis, and long-term metronidazole therapy, are being undertaken even though their absolute benefit is yet to be determined. Penetrating disease requires a broader multidisciplinary approach with a particular focus on nutrition, skincare, and intestinal failure management. The current guidance directs toward early surgical intervention for penetrating disease when feasible. Accurate preoperative imaging, medical management of active diseases, and surgical decision-making based on experience and evidence play a key role in success.